Global Trends of Decolonial Governance in Indigenous Peoples Recognition Policy - Armansyah, ‎; Alwi, ‎; Abdullah, Muh. Tang; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
Interest in the recognition and protection of the rights of indigenous people has grown rapidly in the last decade. This study analyzes the development of the concept of decolonial governance in indigenous peoples’ recognition policies through a systematic literature review (SLR) and bibliometric analysis of global publications for the 2019–2024 period. The aim of the study is to identify publication trends, dominant actors, and institutional design principles that support the decolonial paradigm. The SLR method follows the PRISMA protocol with searches in Scopus and Web of Science databases, complemented by quantitative analysis using Bibliometrix and VOSviewer. The results show an exponential increase in publications (150% since 2019), dominated by researchers from North America, Europe, and South Africa. Key themes include structural decolonization, indigenous peoples’ rights, and institutional reform. The Indigenous Peoples Commission’s case study revealed implementation challenges, such as reliance on authority and resources. The geographical gap is characterized by minimal contributions from Southeast Asia and Latin America, as well as a lack of empirical evaluation of critical findings. This article recommends strengthening participatory methodologies and evaluative research to support inclusive institutional design. The findings provide a conceptual basis for the development of inclusive and equitable decolonial policies.